The Difference of Political Participation of Inland Communities and Coastal Communities in Responding to Local Election: Synergy in Combating Covid-19 and Money Politic - Asna Aneta; Abdul Wahab Podungge; Robby Hunawa; Muten Nuna (Publik : (Jurnal Ilmu Administrasi), 2021)
This study is aimed at analyzing the difference in political participation of inland communities and coastal communities in addressing local elections as an embodiment of synergy in combating Covid-19 and money politics. In this qualitative research, the data were analyzed using an interactive model comprising three analysis components: (1) data reduction, (2) data display, and (3) data verification and conclusion drawing. According to the results, the way the coastal communities respond to the local election differs from that of the inland communities regarding sociological perspective. The coastal communities are not so keen on the election as they concentrate more on their fishing activities. On top of that, people in coastal areas spend most of their time at sea; thus, issues regarding the election are not that impactful for them. The inland communities, on the other hand, has different views thanks to their gregarious characteristic. All their activities and work-life are centralized in a workgroup, enabling the people to have ample time to find out their local leader candidates. This aspect underlines the reason for pluralism among inland communities’ political views, confirming the characteristic of individualism among people in coastal areas.